Exploring the Cultivable Ectocarpus Microbiome - KleinJan, Hetty; Jeanthon, Christian; Boyen, Catherine; Dittami, Simon M. (Frontiers in Microbiology, 2017)
Coastal areas form the major habitat of brown macroalgae, photosynthetic multicellular eukaryotes that have great ecological value and industrial potential. Macroalgal growth, development, and physiology are influenced by the microbial community they accommodate. Studying the algal microbiome should thus increase our fundamental understanding of algal biology and may help to improve culturing efforts. Currently, a freshwater strain of the brown macroalga Ectocarpus subulatus is being developed as a model organism for brown macroalgal physiology and algal microbiome studies. It can grow in high and low salinities depending on which microbes it hosts. However, the molecular mechanisms involved in this process are still unclear. Cultivation of Ectocarpus-associated bacteria is the first step towards the development of a model system for in vitro functional studies of brown macroalgal-bacterial interactions during abiotic stress. The main aim of the present study is thus to provide an extensive collection of cultivable E. subulatus-associated bacteria. To meet the variety of metabolic demands of Ectocarpus-associated bacteria, several isolation techniques were applied, i.e. direct plating and dilution-to-extinction cultivation techniques, each with chemically defined and undefined bacterial growth media. Algal tissue and algal growth media were directly used as inoculum, or they were pretreated with antibiotics, by filtration, or by digestion of algal cell walls. In total, 388 isolates were identified falling into 33 genera (46 distinct strains), of which Halomonas (Gammaproteobacteria), Bosea (Alphaproteobacteria), and Limnobacter (Betaproteobacteria) were the most abundant. Comparisons with 16S rRNA gene metabarcoding data showed that culturability in this study was remarkably high ( 50%), although several cultivable strains were not detected or only present in extremely low abundance in the libraries. These undetected bacteria could be considered as part of the rare biosphere and they may form the basis for the temporal changes in the Ectocarpus microbiome.